MicroRNA 182 promotes T helper 1 cell by repressing hypoxia induced factor 1 alpha in experimental autoimmune encephalomyelitis. Issue 12 (30th September 2019) - Wan, Cong; Bi, Wuchun; Lin, Peng; Zhang, Yun; Tian, Jiangtian; Fang, Shaohong; Li, Zhaoying; Wang, Xi; Qu, Yinan; Mu, Lili; Wang, Jinghua; Kong, Qingfei; et al.
Abstract: MicroRNA 182 is important for the clonal expansion of CD4 + T cells (Th) following IL‐2 stimulation and is a potential therapeutic target for autoimmune diseases. In the present study, we investigated the role of microRNA 182 in the differentiation of pro‐inflammatory CD4 + T helper cell by overexpressing or silencing microRNA 182 expression both in in vivo and in vitro settings. We report that in the studied Chinese cohort, microRNA 182 is upregulated in patients with relapse and remitting multiple sclerosis (RRMS) and this upregulation is associated with increased IFN‐γ producing CD4 + Th1 cells in the circulation. In the murine experimental autoimmune encephalomyelitis (EAE) model, global microRNA 182 overexpression exacerbates clinical symptoms and results in augmented CD4 + IFN‐γ + Th1 and CD4 + IL‐17 + Th17 differentiation in vivo. Addition of microRNA 182 mimics in vitro represses both the protein expression and transcriptional activity of hypoxia induced factor 1α (HIF‐1α) but increases the level of IFN‐γ transcripts in sorted murine CD4 + T cells. Together, our results provide evidence that microRNA 182 may be one of the transitional hubs contribution to regulate Th cells expansion in response to self‐antigens and differentiation of antigen specific Th cells during the progression of autoimmune inflammations. Abstract : microRNA‐182 was increased in the circulating Th cells which associated with Th17 and Th1 increasing during MS and EAE. Hif‐1α might be a negative regulator of Th1 differentiation. microRNA‐182 has the binding site with Hif‐1α mRNA and could down‐regulate Hif‐1α level. Thus microRNA‐182 further promote the differentiation of Th1 cells.